2016
DOI: 10.1155/2016/7602347
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Design and Development of a Unani Transdermal Patch for Antiemetic Therapy and Its Pharmaceutical Evaluation

Abstract: The Transdermal Drug Delivery System (TDDS) is one of the novel routes for systemic delivery of drugs through intact skin. A transdermal patch (TP) is a medicated patch that is placed on skin for delivery of medication through skin into the blood stream. The aim of present study was to formulate and evaluate a Unani transdermal patch that could be used for antiemetic therapy. The incorporation of Unani ingredients, namely, Khardal (Brassica nigra), Zanjabeel (Zingiber officinale), Podina (Mentha arvensis), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
0
15
0
1
Order By: Relevance
“…The comparative permeation study was performed using egg membrane following a reported procedure with slight modifications [32]. Egg membrane has similar properties to stratum corneum of human skin [33,34].…”
Section: Permeation Studymentioning
confidence: 99%
“…The comparative permeation study was performed using egg membrane following a reported procedure with slight modifications [32]. Egg membrane has similar properties to stratum corneum of human skin [33,34].…”
Section: Permeation Studymentioning
confidence: 99%
“…The eggshell membrane was used to evaluate the prepared formulations for the permeation study because it is similar to the stratum corneum of human skin [ 27 , 28 ]. The eggs were procured from a poultry house and dipped into concentrated 0.1 N HCl.…”
Section: Methodsmentioning
confidence: 99%
“…The in-vitro permeation study of BT-NPop and BT-NPopG was done by using the eggshell membrane. Egg membrane having a similar property to stratum corneum of human skin (Kunzi-Rapp et al., 1999 ; Saleem & Idris, 2016 ). The eggs used for the study were incubated at 37 °C to prepare the CAM.…”
Section: Methodsmentioning
confidence: 99%